DEVELOPMENT OF E-MODULE: PREVENTING FICTITIOUS INVESTMENTS AND IT’S IMPACT TO UNDERSTANDING FINANCIAL MANAGEMENT - Arreski, Dwi Fitra; Qaniah, Fadhilah Ahmad (Journal Economics Technology And Entrepreneur, 2025)
Indonesia has experienced a significant increase in cases of fictitious investments, resulting in losses of trillions of rupiah, indicating low financial literacy. This study aims to develop an e-module to prevent fictitious investments and analyze its impact on students' understanding of financial management. The study used a Research and Development (R&D) method with the ADDIE model. The subjects were 87 Economics students selected through purposive sampling. Data were collected through expert judgment validation and a pretest-posttest, then analyzed using a Paired T-Test. Expert judgment validation indicated the e-module was suitable for use, with an average score of 4.4 on a scale of 5. Effectiveness testing demonstrated a significant increase in financial management understanding, from a mean pretest score of 3.44 to a posttest score of 8.98 (p<0.05). The e-module's effectiveness is supported by three main factors: accessibility that allows for self-directed learning, interactivity through quizzes and case simulations, and contextuality using real-life case studies of fraudulent investments in Indonesia. The e-module to prevent fictitious investments proved effective in significantly improving students' understanding of financial management